2023
DOI: 10.1021/acs.cgd.3c00043
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Surface Effects on the Crystal Nucleation and Growth of Clotrimazole Polymorphs

Abstract: Molecules at the surface are spatially different compared to those in the bulk and potentially influence crystallization. In this study, surface effects on crystallization behaviors of two clotrimazole (CMZ) polymorphs were investigated. Form 2 of CMZ is favored to nucleate both at the surface and in the bulk. The nucleation rates of CMZ polymorphs at the surface are vastly accelerated by 5−6.5 orders of magnitude compared to their bulk nucleation rates. The surface-accelerating effect on the nucleation rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The surface chemistry of PA, which includes polar acrylate groups, may facilitate different interactions at the polymer–water interface, impacting the crystallization behavior as shown in studies on the crystallization of amorphous drugs influenced by polymers 43 accounting for the different biomineralization coverage observed. The amide groups of PA can significantly affect surface interactions with the crystallization dynamics, 44 potentially leading to varied coating thickness and crystal morphology.…”
Section: Resultsmentioning
confidence: 99%
“…The surface chemistry of PA, which includes polar acrylate groups, may facilitate different interactions at the polymer–water interface, impacting the crystallization behavior as shown in studies on the crystallization of amorphous drugs influenced by polymers 43 accounting for the different biomineralization coverage observed. The amide groups of PA can significantly affect surface interactions with the crystallization dynamics, 44 potentially leading to varied coating thickness and crystal morphology.…”
Section: Resultsmentioning
confidence: 99%
“…However, amorphous solids tend to crystallize because of their higher energy, thus losing the advantages in solubility and dissolution (Zhang, Guo et al, 2023). More importantly, recent studies revealed that crystallization can be much faster at a free surface or interface in comparison with the rates in the interior of amorphous pharmaceutical solids (Shi, Tao et al, 2020;Yu, 2016;Zhang, Xu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used clotrimazole (CMZ) as a model drug and investigated the impact of P407 on the crystallization of CMZ. CMZ is an antimycotic imidazole agent and is commonly used for studying crystallization [ 24 , 25 ]. Two polymorphs (Form 1 and Form 2) of CMZ have been reported [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…CMZ is an antimycotic imidazole agent and is commonly used for studying crystallization [ 24 , 25 ]. Two polymorphs (Form 1 and Form 2) of CMZ have been reported [ 24 , 25 ]. The metastable Form 2 can only be obtained from melt crystallization and may transform to Form 1 during the melt crystallization [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation